Virtual scenarios of demographic impact on economic growth - Kolyada, Yu.; Poznyak, S. (Економічний вісник Донбасу, 2024)
On the basis of various computer models (classical one-dimensional and author's multidimensional – systems of equations) of nonlinear economic dynamics, the demographic impact on economic growth scenarios is studied, but in the presence of a dynamic modification of the static, as a rule, population growth rate of society. The main objective of the article is to transform the demographic impact from the use of a static population growth rate to a dynamic one, for which purpose the author used the Verhulst model, which allows for a more accurate accounting of changes in the size and structure of the population over time. The study was conducted on real data from 150 countries, covering different stages of economic development, socioeconomic conditions and demographic characteristics. A number of metrics were used to evaluate the accuracy of the models, including the coefficient of determination, MAE, MRE, MSE, RMSE, MSLE, and RMSLE. The results of comparing these metrics allow us to draw conclusions about the effectiveness of using the dynamic population growth rate in modeling the economic growth of society. The article clearly demonstrates that the aforementioned dynamic approach can significantly improve the accuracy of forecasts and better reflects the real trajectory of the economies of different countries, in particular in the context of a changing demographic background. На підставі різноманітних комп’ютерних моделей (класичних одновимірних та авторських багатовимірних – систем рівнянь) нелінійної економічної динаміки досліджується демографічний вплив на сценарії зросту економіки, але за наявності динамічної модифікації статичного, як правило, коефіцієнта приросту населення суспільства. Основною ціллю статті є трансформація демографічного впливу з використання статичного коефіцієнта зростання населення в динамічний, для досягнення якої було застосовано модель Ферхюльста, котра дозволяє більш точно врахувати зміни в чисельності та структурі населення протягом певного часу. Дослідження проводилось на реальних даних 150 країн світу, охоплюючи різні етапи економічного розвитку, соціально-економічні умови та демографічні характеристики. Використано ряд метрик для оцінки точності моделей, зокрема коефіцієнт детермінації, MAE, MRE, MSE, RMSE, MSLE та RMSLE. Результати порівняння цих метрик дозволяють зробити висновки про ефективність застосування динамічного коефіцієнта зростання населення, моделюючи економічне зростання суспільства. Стаття наочно демонструє, що згадуваний вище динамічний підхід дозволяє значно підвищити точність прогнозів і краще відображає реальну траєкторію розвитку економік різних країн, зокрема в умовах змінюваного демографічного фону.